Perlindungan Hukum Terhadap Penerapan Asas Pari Passu Prorata Partij Terhadap Kreditor Konkuren Dalam Perspektif Hukum Acara Perdata - Jayadi, Hendri (Fakultas Syariah INSURI Ponorogo, 2021)
The principle of pari passu prorata partij is applied in bankruptcy cases involving several creditors and debtors. This encourages a study of legal protection for the application of the pari passu prorata partij principle to concurrent creditors in the perspective of civil procedural law. The purpose of this study is to determine the extent to which the principle of pari passu prorata partij provides legal protection for concurrent creditors. The research method used is a qualitative type of literature study. The results of this study indicate that the principle of pari passu prorata partij provides a solution that the provision of repayment to creditors is given jointly without anyone taking precedence, especially concurrent creditors who do not have privileges in accordance with the provisions of the law. Debt repayments to creditors are also scaled according to their relative debt. According to Article 37 of Law no. 37 of 2004, if the debtor's assets are not sufficient to cover his debts, then the curator will make more efforts by filing an actio paulina case. It can be concluded that the principle of pari passu prorata partij can provide solutions and legal protection for bankruptcy problems involving both parties.